Spectrum of Corpus Callosum Agenesis - J Gordon Millichap (Pediatric Neurology Briefs, 2005)
Magnetic resonance imaging and clinical features of 16 children with agenesis of the corpus callosum (ACC) are reviewed at UAE University, United Arab Emirates.